RETROSPECTIVE CLINICAL AND STATISTICAL ANALYSIS OF OVARIAN NEOPLASMS AND TREATMENT OUTCOMES (Symposium on Natural and Applied Sciences, 2026)
Ovarian neoplasms remain a significant issue in modern gynecology due to their high prevalence, variable clinical presentation, and challenges in early diagnosis. This retrospective study evaluates trends in incidence, clinical features, morphological structure, and treatment outcomes among patients with ovarian tumors.